Multicenter Study of Epidemiological Cutoff Values and Detection of Resistance in Candida spp. to Anidulafungin, Caspofungin, and Micafungin Using the Sensititre YeastOne Colorimetric Method - Espinel-Ingroff, A. (Antimicrob Agents Chemother, 2015)
Neither breakpoints (BPs) nor epidemiological cutoff values (ECVs) have been established for Candida spp. with anidulafungin, caspofungin, and micafungin when using the Sensititre YeastOne (SYO) broth dilution colorimetric method. In addition, reference caspofungin MICs have so far proven to be unreliable. Candida species wild-type (WT) MIC distributions (for microorganisms in a species/drug combination with no detectable phenotypic resistance) were established for 6,007 Candida albicans, 186 C. dubliniensis, 3,188 C. glabrata complex, 119 C. guilliermondii, 493 C. krusei, 205 C. lusitaniae, 3,136 C. parapsilosis complex, and 1,016 C. tropicalis isolates. SYO MIC data gathered from 38 laboratories in Australia, Canada, Europe, Mexico, New Zealand, South Africa, and the United States were pooled to statistically define SYO ECVs. ECVs for anidulafungin, caspofungin, and micafungin encompassing ≥97.5% of the statistically modeled population were, respectively, 0.12, 0.25, and 0.06 μg/ml for C. albicans, 0.12, 0.25, and 0.03 μg/ml for C. glabrata complex, 4, 2, and 4 μg/ml for C. parapsilosis complex, 0.5, 0.25, and 0.06 μg/ml for C. tropicalis, 0.25, 1, and 0.25 μg/ml for C. krusei, 0.25, 1, and 0.12 μg/ml for C. lusitaniae, 4, 2, and 2 μg/ml for C. guilliermondii, and 0.25, 0.25, and 0.12 μg/ml for C. dubliniensis. Species-specific SYO ECVs for anidulafungin, caspofungin, and micafungin correctly classified 72 (88.9%), 74 (91.4%), 76 (93.8%), respectively, of 81 Candida isolates with identified fks mutations. SYO ECVs may aid in detecting non-WT isolates with reduced susceptibility to anidulafungin, micafungin, and especially caspofungin, since testing the susceptibilities of Candida spp. to caspofungin by reference methodologies is not recommended.